Pengaruh Pendidikan Matematika Realistik Terhadap Prestasi Belajar Matematika Dengan Kovariabel Bakat Numerik Pada Siswa Kelas V SD Gugus Banyuning - I Putu Suardipa; Ni Nyoman Lisna Handayani (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
This research aims to investigate the effect of realistic mathematic education implementation toward mathematic learning achievement with numerical aptitude covariable of fifth grade students cluster V Banyuning. The research was a quasi-experiment with Posttest-Only Control-Group Design. Research population was the entire fifth grade students of cluster V Banyuning which consisted of 136 students. Research results show that: First, there was a difference in mathematic learning achievement between students who followed realistic mathematic education and students who followed conventional learning model (F = 17.537 with p < 0.05). Second, there was a difference in mathematic learning achievement between students who followed realistic mathematic education and students who followed conventional learning model after numerical aptitude covariable was controlled (F= 23.440 with p<0.05). Third, there was a contribution of numerical aptitude of 29,7% toward students mathematic learning achievement. Keywords: learning achievement, numerical talent, realistic mathematic education